РЕКОМЕНДАЦИИ ПО СОЗДАНИЮ КОЛЛЕКЦИИ В ЭТНИЧЕСКОМ СТИЛЕ - Хапизов, Е.И. (My University, 2019)
Аннотация В данной статье рассматриваются проблемы и особенности создания коллекции в процессе дизайн-проектирования, актуализация поэтапного планирования разработки кол- лекции, влияние этнического стиля на творчество дизайнера костюма. Также анализируется процесс развития этнотенденций, как показатель размытия границ между культурными зо- нами. Abstract This article discusses the problems and features of creating a collection in the design design process, the actualization of the phased planning of the collection, the influence of ethnic style on the costume designer’s work. It also analyzes the process of developing ethnic tendencies, as an indicator of the blurring of boundaries between cultural zones.
Recommendations on creating a collection in ethnic style
Keywords: дизайн-проектирование костюма; этнический стиль; дизайн одежды; создание коллекции; costume design design; ethnic style; fashion design; collection creation